Wind Tunnel Making in Practise - Kostyák, Attila; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2017)
In this paper, we examined the low speed wind-tunnels. Our goal is to construct an open flow system windtunnel that can be utilized in our measurements. To make such a wind-tunnel we needed to build a prototype and calibrated with the help of measurements. Than we determined the flow at the area of measurement. Finally results of the measurements satisfied our expectations. Although there is still much more in development that we would like to do based on the newly gained experience.